Critical Digital Pedagogy in Higher Education - Veletsianos, George; Köseoğlu, Suzan; Rowell, Chris (Issues in Distance Education, 2023)
Recent efforts to solve the problems of education-created by neoliberalism in and out of higher education-have centred on the use of technology that promises efficiency, progress tracking, and automation. The editors of this volume argue that using technology in this way reduces learning to a transaction. They ask administrators, instructors, and learning designers to reflect on our relationship with these tools and explore how to cultivate a pedagogy of care in an online environment. With an eye towards identifying different and better possibilities, this collection investigates previously under-examined concepts in the field of digital pedagogy such as shared learning and trust, critical consciousness, change, and hope.